1998
DOI: 10.5144/0256-4947.1998.389
|View full text |Cite
|
Sign up to set email alerts
|

The Angiotensin-Converting Enzyme (ACE) Gene Insertion/Deletion Dimorphism Tracks with Higher Serum ACE Activities in Both Younger and Older Subjects

Abstract: Background:The absence of a 287 base pair alu sequence in the ACE gene (D allele) is associated with higher ACE levels than its presence (I allele) in adults. We carried out a case-control study of the ACE*I/D dimorphism in relation to circulating ACE activities to evaluate associations between the two variables in adults, compared to younger (18 years or less) individuals. Materials and Methods: Genotypes of the ACE*I/D dimorphism were determined on DNA samples from a population of 164 random (unrelated) Emir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It is suggested that about half of the interindividual difference in ACE levels may be accounted for its polymorphism (19,20). It is reported that mean ACE levels were lowest for II homozygotes, highest for DD homozygotes, and intermediate for ID heterozygotes (18,21). Danser et al explained the higher ACE levels observed in subjects with D allele than those with the II genotype by the sequence harbored in the insert of ACE gene.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that about half of the interindividual difference in ACE levels may be accounted for its polymorphism (19,20). It is reported that mean ACE levels were lowest for II homozygotes, highest for DD homozygotes, and intermediate for ID heterozygotes (18,21). Danser et al explained the higher ACE levels observed in subjects with D allele than those with the II genotype by the sequence harbored in the insert of ACE gene.…”
Section: Discussionmentioning
confidence: 99%
“…ACE converts the inactive angiotensin I into the vasoactive and aldosterone-stimulating octapeptide angiotensin II, as well as causing the inhibition of bradykinin. For these reasons, the ACE gene has been a preferred target in unraveling the molecular complex structure of cardiovascular diseases [ 17 , 18 ]. It was found that the ACE insertion/deletion (I/D) gene polymorphism (rs4340) is a 287 bp sequence of DNA in intron 16 of the ACE gene on chromosome 17q23, whereas there are a few polymorphisms that are in an unbalanced linkage at (rs4646994) in some populations [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin converting enzyme (ACE) is a key component within the RAS and ACE is a dipeptidyl carboxipeptidase that converts angiotensin-I to the potent vasoconstrictor angiotensin-II and inactivites the vasodilator bradykinin (11,14,12 (5,12,20,23). ACE D allele is considered as the reason behind a higher ACE activity in both old and young populations (10). According to the method of Lindpainther et.al.…”
Section: Investigation Of Angiotensin Converting Enzyme Gene Polymorpmentioning
confidence: 99%